The role of virulence genes in Campylobacter pathogenicity: a perspective from the Gulf Cooperation Council countries - Mohamed, Mohamed-Yousif Ibrahim; Khalifa, Hazim O.; Habib, Ihab (Frontiers in Cellular and Infection Microbiology, 2025)
Campylobacter spp., primarily C. jejuni and C. coli, are leading causes of bacterial gastroenteritis worldwide. This review provides an overview of literature on the prevalence and distribution of virulence genes in C. jejuni and C. coli isolated from both food samples and humans across GCC countries. The reviewed evidence highlights a gap in our understanding of how differences in the virulence profile affect the pathogenicity of Campylobacter. Research has shown that C. coli is the predominant species found in retail chicken carcasses in the UAE, while C. jejuni is more common in chicken carcasses across other GCC countries. Studies also reveal distinct genotypes of C. jejuni and C. coli, each with varying pathogenicity. These findings underscore the need for further research on the role of virulence genes in shaping the pathogenicity of Campylobacter, which is essential for developing effective intervention and control strategies in the GCC region.